2016
DOI: 10.2147/ijn.s109470
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of natural mammary gland tumors in canines and felines using gold nanorods-assisted plasmonic photothermal therapy to induce tumor apoptosis

Abstract: Plasmonic photothermal therapy (PPTT) is a cancer therapy in which gold nanorods are injected at the site of a tumor before near-infrared light is transiently applied to the tumor causing localized cell death. Previously, PPTT studies have been carried out on xenograft mice models. Herein, we report a study showing the feasibility of PPTT as applied to natural tumors in the mammary glands of dogs and cats, which more realistically represent their human equivalents at the molecular level. We optimized a regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…In these studies, we observed that animals with induced or spontaneous tumors were effectively cured with no tumor reoccurrence or metastasis. 14,16,17 Our recent in vitro studies also revealed AuNPs and PPTT inhibit cancer cell migration and invasion. 12,18 However, the mechanism of how AuNPs treatments inhibit cancer cell migration remains largely unresolved.…”
mentioning
confidence: 87%
“…In these studies, we observed that animals with induced or spontaneous tumors were effectively cured with no tumor reoccurrence or metastasis. 14,16,17 Our recent in vitro studies also revealed AuNPs and PPTT inhibit cancer cell migration and invasion. 12,18 However, the mechanism of how AuNPs treatments inhibit cancer cell migration remains largely unresolved.…”
mentioning
confidence: 87%
“…The NIR light capable of deeply penetrating the tissue is transiently applied to the tumor, producing localized heat that could lead to tumor necrosis and apoptosis [3]. PPTT modulation to induce cell apoptosis might be a more favorable option than triggering necrosis, as during necrosis, the broken plasma membrane leads to the leaking of cytoplasmic components and inflammation, which could further induce cancer growth and metastasis [4,5,6,7]. The high efficiency of PPTT in getting rid of cancer cells by inducing apoptosis has been demonstrated both in vitro and in vivo [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…In many animal cases, the tumors often metastasize. We have shown the efficacy of this treatment in tumor-bearing mice [8,11] and have recently demonstrated the treatment of mammary carcinoma in dogs and cats, where the malignant mammary tumors of ≤20 cm 3 in volume could be treated by intratumoral inoculation of AuNRs, followed by PPTT [5]. During these studies, we observed that animals with induced or spontaneous tumors have noteworthy regression without any recurrence nor metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the mode of cell death was thought to be apoptosis. Ali et al 114 developed a mild PTT strategy to induce cancer cell apoptosis, by fixing the GNRs concentration (7.5 nM), laser power (5.8 w/ cm 2 ) and adjusting the laser exposure time. They irradiated the human breast cancer (MCF-7) cells and found that after 2 min laser exposure, the cells mainly apoptosis (42.7% apoptosis and 2.89% necrosis), while 5 min laser exposure led to a significant increase in necrosis cells (20.17% apoptosis and 15.5% necrosis).…”
mentioning
confidence: 99%